2017
DOI: 10.20944/preprints201704.0054.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Energy Rebound Effect for Construction Industry: Empirical Evidence from the China

Abstract: Abstract:As the largest energy consumer and carbon emitter, China has made substantial efforts to improve energy efficiency for decrease energy consumption, while the energy rebound effect determines its effectiveness. The embodied energy consumption of construction projects accounted for nearly one-sixth of the total economy's energy consumption in China. This paper is based on the logical relationship among capital input, technological progress, economic growth, and energy consumption, adapting an alternativ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Lu et al [22] studied the energy rebound effect of 135 business divisions in China and found that enterprises could better reduce the energy rebound effect by means of improving the electricity consumption proportion to total energy consumption. Du et al [23] revealed that the average energy rebound effect for the construction industry in China was about 59.5% during the period of 1990-2014. Wu et al's [13] empirical results based on the panel data of various industries sector in Taiwan showed that sectors with lower energy efficiency had higher direct rebound effects, while sectors with higher forward linkages generated higher indirect rebound effects.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al [22] studied the energy rebound effect of 135 business divisions in China and found that enterprises could better reduce the energy rebound effect by means of improving the electricity consumption proportion to total energy consumption. Du et al [23] revealed that the average energy rebound effect for the construction industry in China was about 59.5% during the period of 1990-2014. Wu et al's [13] empirical results based on the panel data of various industries sector in Taiwan showed that sectors with lower energy efficiency had higher direct rebound effects, while sectors with higher forward linkages generated higher indirect rebound effects.…”
Section: Introductionmentioning
confidence: 99%